Etos Transmigran Muslim: Telaah Psikologi - Qodir, Abdul (LP2M IAIN Palangka Raya, 2009)
The objective of this study is to describe and understand the educational ethos phenomena to the transmigrans perception in Pangkoh Village. The educational ethos is a fundamental to create good character, habit, and attitude. Understanding of the individual motivation of this study used Abraham Maslow theory, McClelland theory, and Imam Ghazaly theory.This study used phenomenologic and naturalictic theory. Its purpose is to understand and describe the psychological the phenomena. The findings showed that some transmigrans (father, mother, and their children) have big educational ethos. It seems that they have a plan to change their life getting better. The implication of ethos, they have got good motivation to get success.Â